2020
DOI: 10.1016/j.hpb.2019.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative acute necrotizing pancreatitis of the pancreatic remnant (POANP): a new definition of severe pancreatitis following pancreaticoduodenectomy

Abstract: Background: Recent studies have suggested acute pancreatitis as a separate pancreatic-specific complication following pancreaticoduodenectomy. However, data on necrotizing pancreatitis of the pancreatic remnant is limited. This study aimed to evaluate parameters of patients undergoing completion pancreatectomy (CP) after initial pancreaticoduodenectomy (PD) and compare those with or without necrosis of the pancreatic remanent. Methods: Patients who underwent CP following PD between January 2005 and December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 20 publications
(21 reference statements)
0
32
0
Order By: Relevance
“…The presence of an ischemic/inflammatory process of the pancreatic remnant was suggested as the etiology in several pathologic reports, particularly in series considering operative revisions for Grade C POPF 11,20,37 . These patients indeed represent the most severe and rare scenarios of PPAP (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The presence of an ischemic/inflammatory process of the pancreatic remnant was suggested as the etiology in several pathologic reports, particularly in series considering operative revisions for Grade C POPF 11,20,37 . These patients indeed represent the most severe and rare scenarios of PPAP (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…2). The pathologic findings indicative of PPAP included in such cases acute necrotizing pancreatitis in 41% to 57% of surgical specimens of completion pancreatectomies for grade-C POPF 11,37 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result provided a possible explanation for the polarization of PPAP incidence in the literature. Recent study ( 27 ) showed that necrotizing pancreatitis of the remnant pancreas confirmed by histological section was found in 33 out of 79 (41%) patients who underwent completion pancreatectomy after initial PD due to unfavorable complications. The postoperative pancreatitis not only occurred in the PD or other partial pancreatectomy but also was reported in scoliosis surgery ( 28 ), aortic dissection ( 29 ), renal transplantation ( 30 ), and gynecologic and obstetric surgery ( 31 ), and the incidence ranged from 0.29% to 5.9%.…”
Section: Discussionmentioning
confidence: 99%